Growing Season Lengthens in a North American Deciduous Woody Community From 1993 to 2021 - Carol K. Augspurger; David N. Zaya (Ecology and Evolution)
ABSTRACT Observations of both spring and autumn phenological events were made annually over 29 years (1993–2021) for 22 taxa of multiple growth forms in a mature deciduous forest remnant near Urbana, Illinois, USA. Temporal trends in event dates, trends in stage durations, and associations with weather variables were analyzed with linear mixed‐effect models. Species were grouped together in analyses based on seasonality. Spring event dates for most species advanced from 1.2 to 3.0 days/decade, while durations of spring stages shortened from 0.3 to 0.6 days/decade. Autumn event dates for most species delayed from 1.2 to 3.3 days/decade, while durations of autumn stages lengthened from 0.8 to 3.8 days/decade. Overall, the duration of the growing season lengthened for 88% of species (mean of 4.7 days/decade), with greater delays in autumn phenology for canopy trees and greater advances in spring phenology for other woody life forms. In spring, warmer mean daily temperatures were associated with advances in dates of phenological events. In autumn, minimum daily temperature in the preceding month(s) had the highest predictive power for seasonal groups, except those with Aesculus glabra. In autumn, most species had both a delay in phenology and a strong weather predictor, minimum daily temperature in September, that increased significantly through 29 years. In spring, some concordance between advancing event dates and warming spring temperatures were evident after removing data from 2018 to 2021 with especially high variability in spring temperatures. This study supports the hypothesis that climate change is showing a pronounced association with a delay in autumn leaf coloration, and less so an advance of spring leaf expansion. These changes can affect ecological processes, including plant productivity and carbon uptake/storage, assembly of communities, interactions between trophic levels, and species ranges and invasions.